2021
DOI: 10.1002/lsm.23439
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Pilot Study: Combined 595‐nm Pulsed Dye Laser Treatment and Oxymetazoline Hydrochloride Topical Cream Superior to Oxymetazoline Hydrochloride Cream for Erythematotelangiectatic Rosacea

Abstract: Background and Objectives We evaluated if oxymetazoline therapy combined with 595‐nm pulsed dye laser (PDL) will be more beneficial than topical oxymetazoline alone for the improvement of erythematotelangiectatic rosacea. Study Design/Materials and Methods This was a randomized, controlled, prospective clinical trial approved by an independent Institutional Review Board, which enrolled 34 patients with moderate to severe clinical erythema (CEA) into a two‐arm study of PDL with concomitant oxymetazoline cream (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Recently, some studies showed that even the treatment of combining topical Oxymetazoline cream with energy-based therapy (pulsed dye laser or potassium titanyl phosphate or intense pulsed light) was also safe and well tolerated for the patients. [21][22][23] With regard to the dermal tolerability, compared to the vehicle, Oxymetazoline cream 1.0%…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some studies showed that even the treatment of combining topical Oxymetazoline cream with energy-based therapy (pulsed dye laser or potassium titanyl phosphate or intense pulsed light) was also safe and well tolerated for the patients. [21][22][23] With regard to the dermal tolerability, compared to the vehicle, Oxymetazoline cream 1.0%…”
Section: Discussionmentioning
confidence: 99%
“…At the short-term and long-term follow-up visits, five-point global aesthetic improvement scale (GAIS) was assessed by two blinded investigators (excellent improvement; good improvement; moderate improvement; slight improvement; no improvement). 17 Patient satisfaction was scored on the last visit using a quintile grading scale (excellent; good; fair; little or no change; and aggravated). Any adverse events during the study period were documented.…”
Section: Methodsmentioning
confidence: 99%
“…A higher number indicates more severe redness, therefore, decrease in erythema index means improvement of the erythema. At the short‐term and long‐term follow‐up visits, five‐point global aesthetic improvement scale (GAIS) was assessed by two blinded investigators (excellent improvement; good improvement; moderate improvement; slight improvement; no improvement) 17 . Patient satisfaction was scored on the last visit using a quintile grading scale (excellent; good; fair; little or no change; and aggravated).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, pulsed dye laser (PDL) has been widely used to treat rosacea-related erythema and telangiectasia ( 13 , 14 ). PDL emits pulsed laser energy at wavelengths of 585 or 595 nm, which is absorbed by oxyhemoglobin to inhibit endothelial cell formation, reduce angiogenesis, and destruct the existing vessels ( 15 ).…”
Section: Introductionmentioning
confidence: 99%